Emotional Intelligence and Smash Hit Accuracy: A Correlational Study on Badminton Athletes - Irwanto, Satrio Francesci; Komarudin, Komarudin; Saputra, Mochamad Yamin; Novian, Geraldi (Jurnal Saintifik (Multi Science Journal), 2025)
Emotional intelligence is very important for athletes, especially during the match, good emotional management is needed. The purpose of this study was to determine how emotional intelligence affects the accuracy of the smash of SGS PLN Bandung Badminton athletes. The method used was descriptive with a quantitative approach involving 15 SGS PLN Bandung Badminton athletes. The research instrument was an emotional intelligence questionnaire and a smash accuracy test. The results of the percentage of emotional intelligence and badminton smash accuracy showed that 76.9% of 15 SGS PLN Bandung athletes had a good emotional intelligence presentation and 49.1% of the results of the smash accuracy test. This study concluded that there was a fairly strong and significant relationship between emotional intelligence and smash accuracy, the higher the emotional intelligence, the more precise the smash was.